Validitas Lembar Kerja Peserta Didik untuk Melatihkan Keterampilan Argumentasi Ilmiah Peserta Didik SMA Kelas XI pada Materi Asam Basa - Suparno, Seftany Anggraini; Rusmini, Rusmini (Faculty of Mathematics and Natural Sciences, Universitas Negeri Surabaya, 2023)
Argumentation skills are one of the skills that can help individuals think logically and involve theory and cognitive processes to gain an understanding of scientific concepts and processes. This study aims to determine the validity of the student worksheet to train students' scientific argumentation skills on acid-base material. This research uses the 4D method, namely define, design, develop, and disseminate, but is limited at the develop stage. The results showed the validity of the student worksheet in terms of content, language, presentation, and graphics, with a percentage of 84.33%, 88.33%, 86.66%, and 86.66% on very good category. So, based on this data, the students' worksheet to train argumentation skills using the 4D method is declared valid.